Home bias in humanitarian aid: the role of regional favoritism in the allocation of international disaster relief - Bommer, Christian; Dreher, Axel; Pérez-Alvarez, Marcello (Journal of public economics, 2022)
This paper investigates whether regional favoritism shapes humanitarian aid flows. Using a rich and unique dataset derived from reports of the Office of US Foreign Disaster Assistance (OFDA), we show that substantially larger amounts of aid are disbursed when exogenous natural disasters hit the birth region of the recipient countries’ political leader. While we find no evidence that US commercial or political interests affect the size of this home bias, the bias is stronger in countries with a weaker bureaucracy and governance, suggesting the absence of effective safeguards in the allocation of aid.
Gesehen am 30.08.2022